Marketing communication for temple tourism destinations: from the perspective of post-COVID-19 pandemic visitors - Teguh Dwi Putranto; Daniel Susilo; Tangguh Okta Wibowo (Jurnal Pariwisata Pesona, 2023)
The spread of Corona virus disease-2019 (COVID-19) has had a negative impact on the tourism industry and the creative economy in Indonesia. Since February 2020 the number of foreign visitors coming to Indonesia has decreased. This also has an impact on state revenue in the tourism sector. Coupled with the existence of Large-Scale Social Restrictions (PSBB) and the closure of access to and out of Indonesia, it has also caused a decrease in state revenue in the tourism sector. The purpose of this research is to find out the marketing communication of temple tourism destinations after the COVID-19 pandemic from a visitor perspective. This research is a research with a qualitative approach. Data collection was carried out by interviewing visitors to temple tourism destinations (Prambanan Temple and Ratu Boko Temple). The conclusion from this research is that post-COVID-19 pandemic marketing communications for temple tourism destinations from the visitor's point of view have not been fully implemented. Because based on visitors, word of mouth is the strongest factor for visitors visiting temple tourist destinations.